From myths to markets : essays on gender - Sangari, Kumkum; Chakravarti, Uma.; Indian Institute of Advanced Study (Shimla : Indian Institute of Advanced Study ; New Delhi : Manohar Publishers and Distributors, 1999)
Collection of papers presented at a seminar held in 1993.
Includes bibliographical references.
Keywords: Sex role -- India -- Congresses; Women -- India -- Social conditions -- Congresses; India -- Social conditions -- 1947- -- Congresses